An energy based force prediction method for UD-CFRP orthogonal machining. (1st January 2017) - Li, Hao; Qin, Xuda; He, Gaiyun; Price, Mark A.; Jin, Yan; Sun, Dan
Abstract: The machining of carbon fiber reinforced polymer (CFRP) composite presents a significant challenge to the industry, and a better understanding of machining mechanism is the essential fundament to enhance the machining quality. In this study, a new energy based analytical method was developed to predict the cutting forces in orthogonal machining of unidirectional CFRP with fiber orientations ranging from 0° to 75°. The subsurface damage in cutting was also considered. Thus, the total specific energy for cutting has been estimated along with the energy consumed for forming new surfaces, friction, fracture in chip formation and subsurface debonding. Experiments were conducted to verify the validity of the proposed model.